THE FACTORS CAN MAKE A INFLUENTIAL TO ACCURACY OF PRESENTATION FINANCIAL REPORT - Dina Oktafiya, 08.05.52.0012; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2012)
The Objective of this research is to investigate the empirical evidence about the factors that that affect the timeliness of financial statements on manufacture companies in Indonesian Stock Exchange (IDX) .The research sample was taken from one thousand sixty four listed companies in Indonesian Stock Exchange. These samples were selected by using Puprposive sampling method. Analysis hypothesis is using Multiple Regression model shows that hypotesis test, normality data test using kurtosis Ratio test.The result of Multiple regression model shows that Timeliness influenced by Profitability, Liquidity, Age Company, Firm size, Solvency, Public Ownership.Keyword: Timeliness, Profitability, Liquidity, Age Company, Firm Size, Solvency, Public ownership.